2021
DOI: 10.1007/s00420-021-01735-6
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation and job control predict depressive symptoms: results from the Study on Mental Health at Work

Abstract: Objective Depressive symptoms are a leading cause of disability retirement and sick leave. The aim of this study was to assess the risk of depressive symptoms in German employees and its associations with factors from both the occupational and the non-occupational domain and gender. Methods In the second wave of the German Study of Mental Health at Work (SMGA), a representative sample of 2640 German employees (52% women) was studied. Depressive symptoms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Many secondary analyses of RCTs of IPS have shown that employment mediates the salutary effects of IPS on the nonvocational outcomes. The findings regarding positive effects of competitive employment align with studies in the general population 2,69–72 …”
Section: Effectiveness Of Ipssupporting
confidence: 80%
“…Many secondary analyses of RCTs of IPS have shown that employment mediates the salutary effects of IPS on the nonvocational outcomes. The findings regarding positive effects of competitive employment align with studies in the general population 2,69–72 …”
Section: Effectiveness Of Ipssupporting
confidence: 80%
“… 34 These factors have also been associated with higher risk of musculoskeletal 35 , 36 and mental disorders. 37 , 38 Employees who have low control over their work may experience more musculoskeletal disorders 35 , 36 and depressive symptoms, 37 and employees who perceive an imbalance between their efforts and rewards may have a higher probability to experience musculoskeletal disorders 35 and stress-related mental disorders. 38 …”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of patients referred to secondary care with back and or neck pain found that the perception of support and control at work were associated with disability measured by the Oswestry Disability Index or neck disability index [ 26 ]. A recent study found that low appreciation of superior and low job control was associated with depressive symptoms [ 27 ]. Our study’s results are somewhat in line with this, suggesting that aspects of work support in addition to work demands are connected to treatment outcomes, work ability and disability.…”
Section: Discussionmentioning
confidence: 99%